Use of Ultrasound and Fluoroscopy Guidance in Percutaneous Radiofrequency Lesioning of the Sensory Branches of the Femoral and Obturator Nerves. Issue 4 (9th May 2013) - Chaiban, Gassan; Paradis, Tyler; Atallah, Joseph
Abstract Hip pain is a common condition that is often seen in patients with multiple comorbidities. Often surgery is not an option due to these comorbidities. Percutaneous radiofrequency lesioning of the articular branches of the obturator and femoral nerves is an alternative treatment for hip pain. Traditionally, fluoroscopy is used to guide needle placement. We report a case where a novel approach was used with ultrasound guidance to visualize vascular and soft tissue structures in real time. The use of ultrasound might help to guide the needle to avoid vascular complications due to anatomical variation between patients.